2007
DOI: 10.1103/physrevb.76.075415
|View full text |Cite
|
Sign up to set email alerts
|

Ostwald ripening of faceted two-dimensional islands

Abstract: We study Ostwald ripening of two-dimensional adatom and advacancy islands on a crystal surface by means of kinetic Monte Carlo simulations. At large bond energies the islands are square-shaped, which qualitatively changes the coarsening kinetics. The Gibbs--Thomson chemical potential is violated: the coarsening proceeds through a sequence of `magic' sizes corresponding to square or rectangular islands. The coarsening becomes attachment-limited, but Wagner's asymptotic law is reached after a very long transient… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 77 publications
2
13
0
Order By: Relevance
“…We later confirmed this observation on a liquid crystal Sicilia-etal08 [40] and recent experiments using phase separating glasses (though in 3d) observe a similar phenomenology Bouttes [41]. A morphological analysis along these lines was later performed on the same 2d model with conserved order parameter modelling phase separation SiSaArBrCu09 [20], see also Kaganer07,Takeuchi15 [42,33]. The effect of weak quenched disorder was consider in SiArBrCu08 [43].…”
Section: Number Density Of Finite Areas and Lengthssupporting
confidence: 77%
“…We later confirmed this observation on a liquid crystal Sicilia-etal08 [40] and recent experiments using phase separating glasses (though in 3d) observe a similar phenomenology Bouttes [41]. A morphological analysis along these lines was later performed on the same 2d model with conserved order parameter modelling phase separation SiSaArBrCu09 [20], see also Kaganer07,Takeuchi15 [42,33]. The effect of weak quenched disorder was consider in SiArBrCu08 [43].…”
Section: Number Density Of Finite Areas and Lengthssupporting
confidence: 77%
“…It must be answered to this that the principally essential in the processes of crystal growth and dissolution can also be seen even on the simplest model, quite independently of whether the mentally constructed model is realized in nature or not, provided only that it is void of self-inconsistencies." Such simulations as well as simulations on the Ising model continue to be carried out [14][15][16][17][18][19][20][21][22][23][24][25][26] because usually they are considerably less computer-time consuming than the respective molecular dynamics simulations. They referred to the Kossel crystal model which is a concrete case of the latticegas model known to have one-to-one correspondence with the Ising model of ferromagnets.…”
Section: Introductionmentioning
confidence: 99%
“…The coarsening exponent of n ¼ 1 that was measured in this case implies a strong deviation from classical coarsening theory and from coarsening measured on Si(0 0 1). The explanation for the exotic ''linear'' recovery dynamics measured on GaAs is not yet understood, although kinetic Monte Carlo simulations point to the importance of corner sites of 2D faceted islands for such exotic coarsening behavior [28]. X-ray diffraction studies on GaSb(0 0 1) [22] showed a temperature dependence for the kinetics of sub-ML islands, and at intermediate growth temperatures (385-470 1C) coarsening exponents between 0.27 and 0.40 were measured, suggesting diffusion-limited 2D ripening kinetics.…”
Section: Island Kinetics For 1 2 ML Depositionmentioning
confidence: 98%